Inhibition of acid sphingomyelinase by tricyclic antidepressants and analogons - Beckmann, Nadine; Sharma, Deepa; Gulbins, Erich; Becker, Katrin Anne; Edelmann, Bärbel (Frontiers in Physiology, 2014)
Amitriptyline, a tricyclic antidepressant, has been used in the clinic to treat a number of disorders, in particular major depression and neuropathic pain. In the 1970s the ability of tricyclic antidepressants to inhibit acid sphingomyelinase (ASM) was discovered. The enzyme ASM catalyzes the hydrolysis of sphingomyelin to ceramide. ASM and ceramide were shown to play a crucial role in a wide range of diseases, including cancer, cystic fibrosis, diabetes, Alzheimer's disease, and major depression, as well as viral (e.g., measles virus) and bacterial (e.g., Staphylococcus aureus, Pseudomonas aeruginosa) infections. Ceramide molecules may act in these diseases by the alteration of membrane biophysics, the self-association of ceramide molecules within the cell membrane and the ultimate formation of larger ceramide-enriched membrane domains/platforms. These domains were shown to serve the clustering of certain receptors such as CD95 and may also act in the above named diseases. The potential to block the generation of ceramide by inhibiting the ASM has opened up new therapeutic approaches for the treatment of these conditions. Since amitriptyline is one of the longest used clinical drugs and side effects are well studied, it could potentially become a cheap and easily accessible medication for patients suffering from these diseases. In this review, we aim to provide an overview of current in vitro and in vivo studies and clinical trials utilizing amitriptyline to inhibit ASM and contemplate possible future applications of the drug.